ANALISIS YURIDIS TENTANG KEDUDUKANSAKSI DALAM PEMBUATAN AKTA NOTARIIL MENURUT HUKUM ISLAM DAN UNDANG-UNDANG JABATAN NOTARIS (UUJN) - INTAN MAISYARAH (PREMISE LAW JURNAL, 2016)
Indonesian is a constitutional state, and along with its judicial development the Islamic law is included as a legal source in Indonesia, especially in the civil law. A witness in the Court plays an  important role as evidence. In the Sura Al-Baqarah, verse 282, it is stated that a witness in the Islamic Law consist of two male Moslems or one man and two women. The result of the research showed that the presence of witnesses in the Islamic law is an obligation because a witness is required to make a deed valid although in the Islamic law two female witnesses are equal to one male witness, and  if one of the is absent, people will remind them. Terms manufacture UUJN Notarial deed in accordance with the provisions of islamic law. In the Al-Quran sura Al-baqarah verse 282 there are differences that the witness of two men, and had Islam while in UUJN not so, because it was in the making of a notarial deed in UUJN not based on Islamic law. Keywords: Witnees, Deed, and Notary